군수품 품질수준진단 프레임워크 설계 - 강요한; 최진영 (품질경영학회지, 2024)
Purpose: The purpose of this study was to propose a framework for quality level diagnosis of military supplies, which consists of 7 steps for developing questionnaires and suggesting improvement guidelines. Methods: We analyze the required functions of the equipment under investigation, classify the main components, review quality characteristics, develop a quality level checklist through the first and second stages of quality function deployment, and evaluate and analyze the results of the quality level survey applied to this checklist. Results: We first compared and analyzed case studies of domestic and international military and civilian quality level surveys and proposed a framework for diagnosing the quality levels of military supplies. Additionally, we applied the proposed quality level diagnosis framework to a specific weapon system to analyze its quality characteristics and identify improvement directions, thereby verifying the applicability of the proposed framework for diagnosing the quality levels of military supplies. Conclusion: The results of this study, which include the application of the proposed diagnostic framework for quality investigation and analysis, can be used to understand the satisfaction with the military supplies currently in operation. This will enable the continuous assurance of quality related to the functions and performance required by the military weapon systems.
Keywords: Quality Level Diagnosis Framework; Military Supplies; Quality Function Deployment; Quality Level Checklist